Pravne posledice kršitev korporacijskih pravil glede sklepanja pravnih poslov s povezanimi strankami in funkcionarji gospodarskih družb - Juhart, Miha (Podjetje in delo, 2021)
Legal transactions between the company and related parties have become the subject of special regulations. Breach of special rules on transactions with related parties has legal consequences inside the company and external relationship with related person. This paper examines the legal consequences of a breach in the external relationship. Transactions with related parties are not prohibited, but the consent of the competent company body is required. The breach is primarily the absence of required consent. In this case, transactions should not be made null. The only exceptions are situations where the nullity is justified by some special circumstance. Special attention is paid to business between the company and members of its bodies. At least in some special cases (consulting contracts, loan agreements), in the author's opinion, consent is a condition for the conclusion of a valid contract. In the absence of consent, legal consequences arise as if there is no valid legal basis between the parties. The argument against nullity, however, is the possibility of remedying the deficiencies that result in the validity of the contract.
Keywords: condition; consulting contract; loan; ničnost; nullity; pogoj; posli s povezanimi osebami; posojilna pogodba; related party transactions; svetovalna pogodba